Comparative environmental impact assessment of various fuels and solar heat for a combined cycle - Ozturk, Merve; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In the present study, a comparative life cycle assessment (LCA) for evaluation of the environmental impacts of different fuels to generate electricity through a combined cycle is carried out. For this purpose, various heat sources including solar thermal, lignite, natural gas, oil, and hydrogen are investigated with LCA methods. The methods considered for the study include CML 2001 and ReCiPe Endpoint. The results of the present LCA study for both methods show that the hydrogen is the best fuel option according to the environmental impacts. The impact categories obtained from CML 2001 are the depletion of abiotic resources, eutrophication, global warming, marine sediment, and aquatic ecotoxicity, freshwater aquatic ecotoxicity and the competition of land. Furthermore, the human health, ecosystems and resource availability are investigated with the ReCiPe Endpoint method. The greenhouse gas emissions per kWh electricity generation are 0.19 kg CO2 eq for solar, 1.21 kg CO2 eq for lignite, 0.53 kg CO2 eq for natural gas, 1.11 kg CO2 eq for oil and 0.04 kg CO2 eq for hydrogen according to the CML 2001 method. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Life cycle assessment; Environmental impact; Combined cycle; Hydrogen; Solar energy; Fossil fuels; HYDROGEN-PRODUCTION; POWER-PLANTS; ENERGY; WIND; Chemistry; Electrochemistry; Energy & Fuels